Aplikasi pemberian teknik distraksi terhadap skala nyeri anak selama prosedur medis - Setiawati Setiawati; Linawati Novikasari (Holistik Jurnal Kesehatan, 2021)
A comparison of distractors for  controlling pain and discomfort in young children during medical procedures Background: The problem that often occurs in the pediatric ward is when going to take medical procedures, there are several procedures that will cause a pain and discomfort in young children. During the performance, a nurse needs a full concentration and a calm environment. Meanwhile, a young children need a distraction for controlling pain and discomfort during medical procedures. Procedure need to apply to make easily and smoothly until end of the performance.Purpose:  A comparison of distractors for  controlling pain and discomfort in young children during medical proceduresMethod: A quantitative study and a purposive sampling experimental design (pre-test and post-test). The population and sample taken 60 participants by a purposive sampling divided into two groups intervention, 30 participants by video cartoons and 30 participants with storytelling. A medical procedure when taking a venous blood sample. The measuring instrument used the face, legs, activity, cry and consolability (FLACC) pain scale with the lowest score of 0 and the highest score of 10. Statistical test using the T test.Results: Finding that there was a significant effect on young children by distraction technique with cartoon video media and storytelling media when taking venous blood samples. Both groups obtained p-value 0.000, indicating that both distraction techniques are effective to use. While the difference in the mean value (pre test-post test) on video cartoon media is 0.97 and storytelling media with a mean value of 1.50. It means that storytelling media is more effective than video cartoon media.Conclusion: Both distraction techniques, such as videos, cartoon media and storytelling media, have a significant level of effectiveness and storytelling media is more effective than cartoon video media, that could as an alternative as a permanent procedure in the pediatric ward.Keywords: Distractors; Controlling pain; Discomfort; Young children; Medical proceduresPendahuluan:  Masalah yang sering terjadi diruang anak yaitu pada saat akan melakukan tindakan medis, dimana ada beberapa prosedur yang akan membuat rasa sakit dan ketidaknyamanan pada anak. Selama tindakan tersebut, seorang perawat akan mengerjakannya dengan penuh konsentrasi dan perlu ketenangan. Sedangkan pada anak tersebut dibutuhkan tindakan distraksi supaya tindakan medis dapat dilakukan dengan mudah dan lancar.Tujuan: Untuk melihat efektivitas pemberian teknik distraksi terhadap skala nyeri anak selama prosedur medis di rumah sakitMetode: Penelitian kuantitatif dengan desain eksperimen semu (pre-test dan post-test) dan pemilihan sampelnya menggunakan purposive sampling. Populasi dan sampel sebanyak 60 partisipan yang dibagi dalam dua grop perlakuan yaitu 30 partisipan dengan media video cartoon dan 30 partisipan dengan media storytelling. Prosedur medis yang dilakukan pada saat pengambilan sampel darah vena. Alat ukur yang dipakai untuk mengujkur skala nyeri menggunakan skala nyeri face, legs, activity, cry and consolability (FLACC) dengan skor terendah 0 dan tertinggi skor 10. Uji statistik menggunakan uji T.Hasil: Didapatkan adanya pengaruh yang signifikan pada anak jika dilakukan perlakukan distraksi dengan media video kartun dan media storytelling saat pengambilan sampel darah vena. Kedua kelompok didapatkan p-value 0.000 menunjukkan bahwa kedua intervensi efektif untuk digunakan. Sedangkan perbedaan nilai mean (pre test-post test) pada media video cartoon 0.97 dan media storytelling dengan nilai mean 1.50. artinya media storytelling lebih efektif dibandingkan media video cartoon.Simpulan: Intervensi menonton video kartun dan storytelling mempunyai tingkat efektivitas yang sukup signifikan dan media storytelling lebih efektif dibandingkan media video cartoon, sehingga dapat jadikan alternatif sebagai prosedur tetap diruangan anak.